PENERAPAN ASAS ITIKAD BAIK DALAM PERJANJIAN SEWA-MENYEWA (STUDI TERHADAP PERJANJIAN SEWA MENYEWA OULET DI HERMES BUILDING MEDAN ) - Gary Hadi; Bismar Nasution; Hasim Purba Purba; Utari Maharany Barus (USU LAW JOURNAL, 2017)
ABSTRACT Tenancy agreement in accordance with Article 1548 of the Civil Code has the meaning of an agreement when one party binds itself to provide enjoyment of goods to the other party a certain time , with the payment of a price promised by the latter party . This thesis used a normative study with a descriptive analysis. Application of the principle of good faith in the tenancy agreement Hermes outlet in Medan Building seen from before and after the deal happen. Even the application of the principle of good faith prior to the agreement, PT. Hermes Realty Indonesia has implemented the principle of good faith objective. Criteria breach the principle of good faith in the tenancy agreement Hermes Building outlet in Medan is when wanprestasinya CV. Khansa Independent Asri. The criteria is to have violated an inappropriate thing to do as not carry out its obligations intentionally do not pay rent, service charges and utility costs.   Keywords: Agreements, Rent-hire, principle of good faith